Fly Guy's ninja Christmas - Arnold, Tedd (Arnold, Tedd. Fly Guy., 2016)
It is Christmas Eve and Fly Guy realizes that he does not have a present to give to his best friend Buzz--but when he looks around the house searching for something suitable he discovers a stranger in a red suit, and decides to attack with some ninja moves.